Determination of photophysical, photochemical and spectroscopic properties of novel lead(II) phthalocyanines - ODABAŞ, ZAFER (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
This study presents the synthesis and characterization of novel peripheral and non-peripheral tetra-2,6-dimethoxyphenoxy substituted lead(II) phthalocyanines. They were characterized by elemental analysis, IR, UV-vis, fluorescence, H-1 NMR, C-13 NMR and MALDI-TOF mass spectroscopic techniques, as well as thermogravimetric analysis. Their spectroscopic, photophysical and photochemical properties were studied in dimethylsulfoxide and compared with the above-mentioned properties of lead(II) phthalocyanines containing different substituents reported in the literature. Novel phthalocyanines can be good candidates as photosensitizers for photocatalytic reactions because they possess properties that are important for Type II mechanics, such as low photostability, sufficient singlet oxygen production, high solubility and non-aggregation behavior in commonly known organic solvents. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Heavy metal; Singlet oxygen; Low photostability; METAL-FREE; SUBSTITUENTS; NAPHTHALOCYANINES; PORPHYRINS; SYMMETRY; ZINC(II); CRYSTAL; SOLVENT